Promoting equity in health emergencies through health systems strengthening: lessons learned from disability inclusion in the COVID-19 pandemic - Emma Pearce; Kaloyan Kamenov; Darryl Barrett; Alarcos Cieza (BMC, 2022)
Abstract Discriminatory health systems and inequalities in service provision inevitably create barriers for certain populations in a health emergency. Persons with disabilities have been disproportionately affected by the COVID-19 pandemic. They commonly experience three increased risks - of contracting the disease, of severe disease or death, and of new or worsening health conditions. These added risks occur due to a range of barriers in the health sector, including physical barriers that prevent access to health facilities and specific interventions; informational barriers that prevent access to health information and/or reduce health literacy; and attitudinal barriers which give rise to stigma and exclusion, all of which add to discrimination and inequality. Furthermore, national health emergency preparedness and planning may fail to consider the needs and priorities of persons with disabilities, in all their diversity, thus leaving them behind in responses. This commentary discusses the importance of inclusive health systems strengthening as a prerequisite for accessible and comprehensive health emergency preparedness and response plans that reach everyone. Lessons learned relating to disability inclusion in the COVID-19 pandemic can inform health systems strengthening in recovery efforts, addressing underlying barriers to access and inclusion, and in turn improving preparedness for future health emergencies.